Mecanismos de atenuação e intensificação no ensino-aprendizagem do português como língua estrangeira - Gomes, Carlos (2014)
The present work is the result of an action research project made under the Portuguese as a Foreign Language Master's in FLUP, and consists on the presentation of results arising from a case study centered on the teaching-learning of attenuation and intensification mechanisms, made in a level C class. This action research project aimed at making a pragmatic-linguistic exploration of attenuation and intensification, then, to make a pedagogical-didactic of the two mechanisms under Portuguese as a Foreign Language teaching, and, lastly, to implement on classroom an action plan arising from the research conducted. The results obtained in this work showed a correct and effective application of the attenuation and intensification mechanisms by the learners either in writing or in oral, besides the use of different kinds of these mechanisms that, consequently, resulted in an overall development of communicative competence.